INOVASI PEMBELAJARAN METAMORFOSIS DENGAN WEB GENIALLY: SOLUSI INTERAKTIF UNTUK SISWA KELAS III SD - Fitriah, Ulfa Laelatul; Suciptaningsih, Oktaviani Adhi; Mas'ula, Siti (STKIP Persada Khatulistiwa Sintang, 2025)
Quality elementary education requires effective and engaging learning methods to help students comprehend complex scientific concepts. This study explores the use of interactive digital media, Web Genially, in teaching the topic of metamorphosis within the Natural and Social Sciences (IPAS) subject to third-grade elementary students. Employing a qualitative case study design, the research involved 11 students as participants to examine the impact of Genially on students’ understanding and engagement. Data were collected through observation, interviews, and documentation of learning outcomes, then analyzed descriptively. The findings reveal that Genially significantly enhanced students’ comprehension of metamorphosis stages and fostered active participation in learning. This medium also accommodated diverse learning styles, providing enjoyable and contextual learning experiences aligned with the principles of the Merdeka Curriculum. The integration of the Problem-Based Learning (PBL) model with Genially further strengthened students’ problem-solving and collaboration skills. Technical challenges and limited teacher proficiency could be mitigated through appropriate strategies. Overall, the use of Genially proved to be an effective digital learning innovation that improves the quality of IPAS instruction in elementary schools.